The triadic relationship between spinal posture, loading, and degeneration - Fasser, Marie-Rosa; Furrer, Pascal R.; Fisler, Luca; Urbanschitz, Lukas; Snedeker, Jess G.; Farshad, Mazda; Widmer, Jonas (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionDegenerative changes in the lumbar spine may affect many structures, among them the intervertebral discs and the facet joints. The individual load distribution within the spine linked to posture and mass distribution is a probable cause of disease. This study had a dual aim: first, to systematically summarize previously reported associations between sagittal balance parameters and the occurrence of lumbar spine degeneration. Second, to complement these insights with additional biomechanical findings meant to elucidate the link between spine load and alignment as well as selected demographic descriptors.MethodsA systematic literature search was performed on PubMed to identify clinical studies that quantified the association between spinal alignment and the occurrence of disc herniation, disc degeneration, facet joint degeneration, and spondylolisthesis. Further, a previously published musculoskeletal model was used to link sagittal spinal alignment and subject characteristics to joint loading within the lumbar spine for a cohort of 144 subjects.ResultsThe literature review yielded 49 publications evaluating the relationship between spinal alignment and the occurrence of pathologies in the lumbar spine. The results indicate that a straight spine might negatively affect the health status of the intervertebral disc, likely because of a lack of damping and associated high compressive loads. These loads further show a major dependence on body weight. On the other hand, facet degeneration and spondylolisthesis may be linked to higher anterior-posterior shear forces acting on the relevant spinal structures because of a generally more sagittally curved spine. A straight lumbar spine is more likely to stress the disc, whereas highly curved spines with a high pelvic incidence are more likely to stress the posterior structures. The biggest influencing factors on the resulting force and consequently potentially the wear of the anatomical structures are the intervertebral inclination from an anatomical point of view and the weight from a demographic point of view.DiscussionInformation concerning spinal loading resulting from spinal alignment and body descriptors could impact both conservative treatment and operative planning for patients afflicted by spine disease through targeted changes in posture.